PROBLEMS OF REACTIVE POWER COMPENSATION OF 110 KV LINE CABLE - Pijarski, Paweł; Gryniewicz- Jaworska, Michalina (MATTER: International Journal of Science and Technology, 2017)
Construction of 110 kV cable systems, where the line length exceeds ten kilometers requires compensation of reactive power generated by the cable capacitance. The compensation can be realized with the application of shunt reactors, whose selection seems to be an easy task. The presented considerations deal with a problem, whose source are the below listed facts. Both the 110 kV cable and the shunt reactor to be applied are custom made and their quality parameters are subject to random variability, whose source are manufacturing processes. Construction of a cable system and manufacturing of a customized shunt reactor are realized at the same time and hence it is not possible to have the reactor matching the already existing and tested cable line. Taking into account that cable and reactor parameters are of random character, the shunt reactor selection process exhibits features of a stochastic process. The article presents the Monte Carlo simulation results obtained for various parameters of the analyzed HV cable line – shunt reactor system. Various forms of the random variable distribution have been obtained and the random variable is the operation compensation costs. The performed analyses make it possible to select optimal inductance for the shunt reactor. The highest value of the probability that operation costs of the reactive power compensation will not exceed a certain predefined value has been assumed as the selection criterion.